Answer :

f(x)=2x3-3x2-36x+7


f’(x)=6x2-6x-36


f’(x)=6(x2-x-6)


f’(x)=6(x-3)(x+2)


f’(x) is 0 at x=3 and x=-2



F’(x)>0 for x (-, -2] [3, ∞)


hence in this interval function is increasing.


F’(x)<0 for x (-2 ,3)


hence in this interval function is decreasing.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar